The incidence of tuberculosis cases in the municipality of Santarém, from 2018 to 2020 (Research, Society and Development, 2021)
Tuberculosis (TB) is an infectious and transmissible disease of social evidence being considered a serious public health problem. The objective is to analyze the incidence of TB cases in the city of Santarém, from 2018 to 2020, outlining the profile of those affected by tuberculosis, analyzing the diseases associated with TB. Field research, with a quantitative approach, developed at the Municipal Secretariat of Santarém - SEMSA through the database of the Notifiable Diseases Information System - SINAN, target population notified cases with TB in the period 2018 to 2020. In 2018 to 2020, 575 TB cases were registered in Santarém, with a proportion of 58 cases/100,000 inhabitants. Regarding the profile of those affected, it was observed that in 2019 there was an increase in cases in the age group from 0 to 14 years compared to other years, whereas in the age group of 15 years or more there was a reduction in cases in 2019, there was an increase in this quantitative in 2020. Regarding schooling, the highest prevalence in students from 1st to 4th grade of incomplete primary education, with males being more affected. The most common problems are people who drink, are diabetic, HIV positive and smokers. As a result, the municipality of Santarém has an incidence rate above the national average, and for this reason it is important to develop strategies to fight TB, emphasizing the implementation of educational actions and professional training to serve this public.